Respuesta :

Answer:

for x-intercept, y=0

Step-by-step explanation:

[tex]y = - 4 {x}^{2} + 16x + 20 \\ 0 = - 4 {x}^{2} + 16x + 20 \\divide \: by \: - 4 \\ 0 = {x}^{2} - 4x - 5 \\ {x}^{2} - 4x - 5 = 0 \\ from \: quadratic \: equation \\ x = \frac{ - b± \sqrt{ {b}^{2} - 4ac} }{2a} \\ from \: the \: equation \\ a = 1 \: \: b = - 4 \: \: c = - 5 \\ =x = \frac{ -( - 4)± \sqrt{ {( - 4)}^{2} - (4 \times 1 \times - 5) } }{(2 \times 1)} \\ x = \frac{ 4± \sqrt{26} }{2} \\ x = 2± \sqrt{26} \\ x = 2 + \sqrt{26} \: \: or \: \: 2 - \sqrt{26} \\ x = 7.1 \: or \: x = −3.1[/tex]

x-intercepts are (7.1, 0) and (-3.1, 0)